A school tries to change: How leaders and teachers understand changes to space and practices in a UK secondary school. (July 2014) - Woolner, Pamela; Clark, Jill; Laing, Karen; Thomas, Ulrike; Tiplady, Lucy
This article considers a school community initiating change in pedagogical practices to complement new-build premises in the context of demands for school improvement, but constraints on autonomy. We investigate how school leaders planned the change towards enquiry-based learning in flexible spaces, and how teaching staff prepared for the coming change. We worked with teachers to explore current experiences of teaching and learning in self-contained classrooms where teachers mainly teach alone, and anticipations for the new building, where there will be large, shared spaces, facilitating movement and different groupings of students, encouraging student autonomy and teacher teamwork. Preparation for change was centred on an 'experimental week' of enquiry learning that took place in an existing large space (a school hall). Here we explore the experiences of the teachers involved, particularly their ideas about the potential for changing practices, considering these in light of the plans of the school leaders and of wider understandings of school change. We met the teachers before and after the experimental week, observed the week and conducted interviews mediated by photographs of the week. The tensions and stresses of attempting to make extensive changes to teaching practices were evident, together with suggestions that the school leaders were failing to appreciate the complexity of the change they were planning or to communicate the ideas about it that they had developed. The probable consequences for the school, given the uneven distribution of autonomy in UK schools, are briefly considered.